2017
DOI: 10.1016/s2095-3119(16)61568-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic behavior of Triticum aestivum–Dasypyrum villosum translocation chromosomes T6V#4S·6DL and T6V#2S·6AL carrying powdery mildew resistance

Abstract: T6V#2S•6AL and T6V#4S•6DL translocation chromosomes developed from the cross of wheat and different Dasypyrum villosum accessions have good powdery mildew (PM) resistance, but their pairing and pyramiding behavior remains unclear. Results in this study indicated that the pairing frequency rate of the two different originated 6VS chromosomes in their F 1 hybrid was 18.9% according to genomic in situ hybridization (GISH); the PM resistance plants in the F 2 generation from the cross between T6V#4S•6DL translocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…However, we found that the exchanging frequency between 6V#2S and 6V#4S was very low in this research. Liu, Ye, Wang, Li, and Lin () also observed the low pairing frequency of two translocation chromosomes. It somewhat suggested that the two D. villosum accessions might have been evolved independently, geographically, for a long history.…”
Section: Discussionmentioning
confidence: 91%
“…However, we found that the exchanging frequency between 6V#2S and 6V#4S was very low in this research. Liu, Ye, Wang, Li, and Lin () also observed the low pairing frequency of two translocation chromosomes. It somewhat suggested that the two D. villosum accessions might have been evolved independently, geographically, for a long history.…”
Section: Discussionmentioning
confidence: 91%
“…52 . The seedlings were then covered with preservation film to maintain high humidity and placed in a growth chamber with the same photoperiod as described above and a temperature regime of 22 °C in light/20 °C in darkness.…”
Section: Methodsmentioning
confidence: 99%
“…Current research on D. villosum , including marker development, is mostly focused on the accession D. villosum#2 . Although some preliminary investigations on D. villosum#4 have been performed [11, 22, 31, 37, 39, 56], this genetic resource has not yet been fully exploited and utilized. Developing markers specific to the D. villosum#4 genome will accelerate the application of the potential genes in D. villosum#4 and further expand the genetic background of wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Update, more than 300 D. villosum accessions have been collected from different native habitats, and only a few ( D. villosum #1 to D. villosum #5) have been used to develop wheat- D. villosum chromosome addition, substitution, and translocation lines [621]. There is some genetic divergence among different D. villosum accessions [24, 31, 39]. In this study, we were only able to develop one marker each for 1V and 7V.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation